Effect of nigella sativa on selected menopausal parameters in ovariectomized rats - Parhizkar, Saadat (2009)
Menopause is condition when regular menstrual periods cease and may be accompanied by psychological and physical systems. This is due to ovarian failure and estrogen deficiency which will influence the quality of life. Hormone replacement therapy (HRT) is being used to relieve postmenopausal systems thereby improving the quality of life. Prolonged exposure to HRT, however, gives side effects. As such, Complementary and Alternative Medications (CAMs) is being used as an alternative to HRT. Nigella sativa (black seed) is used to treat various illnesses and improve health status. Its application in menopausal women however has never been scientifically evaluated. Three experiments were conducted to investigate the effects of Nigella sativa (NS) in ovariectomized (OVX) rats (menopause-induced animal model). The first experiment was to determine the effect of Nigella sativa seeds on selected menopause parameters (estrogen levels, uterine histological changes, vaginal epithelial cell cornification) and metabolic status (lipid profile, body weight and blood glucose level) of ovariectomized rats. Forty OVX rats were divided equally into 5 groups and supplemented for 21 days to one of the following treatments: conjugated equine estrogen (CEE, 0.2mg/kg), distilled water, Nigella sativa: low, medium and high doses (300, 600 and 1200mg/kg). The second experiment was conducted to determine the effects of Nigella sativa extracts obtained by different methods of extraction on similar parameters as in experiment one with the exception of uterine histological study. Five groups of eight OVX rats each received of 3000 mg/kg of different extracts of Nigella sativa (Supercritical Fluid Extraction SFE), Methanol and hexane extracts) or CEE (0.2mg/kg) or olive oil (1ml/day) 21 days. The third experiment (consisted of two steps) was to determine the fatty acid composition of Nigella sativa and to investigate the effected of some of its ingredients on similar parameters as in experiment two. In step 1 of this experiment, various extracts of Nigella sativa were analyzed for their fatty acid composition. In step 2, three different chemical components of Nigella sativa (linoleic acid, 50 mg/kg; gamma linolenic acid, 10mg/kg; thymoquinone, 15mg/kg) were given to OVX rats. While CEE (0.02mg/kg) and olive oil (1ml/day) were supplemented to the group. The result of the first experiment showed that CEE or Nigella sativa supplementation increased (p<0.05) uterine weight as compared to the controls (290-500 ± 0.01 vs 190±0.02 mg for NS and CEE vs control). These supplementations also induced histological changes in the uteri (p<0.05) similar to estrogen induced effect (Endometrial thickness: from 281 ±39 to 365 ±123 vs 251± 107 µm for NS and CEE vs control). In addition, low dose of Nigella sativa supplementation was more effective in inducing the estrogenic-like effects as compared to medium and high doses. The second experiment showed that all extracts of Nigella sativa produced estrogen-like effects as compared to the control and the methanolic extract was the most effective (cornification of vaginal epithecell cell percentage 47.62%, 32.87%, 32.46% for methanol, hexane and SFE respectively vs 62% and 00% for positive and negative control respectively). In the third experiment, only linoleic acid showed significant (p<0.05) estrogen-like activities (cornification of vaginal cell percentage 37.92%, 9.50%, 14.62%, 62% for LA, GLA, TQ and CEE respectively vs 00% for control). In this study, Nigella sativa showed estrogen-like effects on the physical, histological and biochemical parameters of OVX rats, thereby indicating the probable beneficial role for the treatment of postmenopausal systems. In conclusion, this study provides novel evidence in support of continuing action of the traditional use of Nigella sativa in menopausal women. The study also suggests the possibility of using Nigella sativa as an alternative to HRT for host menopause in human as indicated in animal model. Future studies are needed to elucidate the principals, mechanism and active ingredients of Nigella sativa on the mammalian reproductive systems.